Fungal Mitogenomes: Relevant Features to Planning Plant Disease Management - Medina, Rocio; Franco, Mario Emilio Ernesto; Bartel, Laura Cecilia; Martinez Alcántara, Virginia; Saparrat, Mario Carlos Nazareno; Balatti, Pedro Alberto (Frontiers in Microbiology, 2020)
Mitochondrial genomes (mt-genomes) are characterized by a distinct codon usage and their autonomous replication. Mt-genomes encode highly conserved genes (mt-genes), like proteins involved in electron transport and oxidative phosphorylation but they also carry highly variable regions that are in part responsible for their high plasticity. The degree of conservation of their genes is such that they allow the establishment of phylogenetic relationships even across distantly related species. Here, we describe the mechanisms that generate changes along mt-genomes, what plays key roles at enlarging the ability of fungi to adapt to changing environments. Within mt-genomes there are dispensable as well as indispensable genes for survival, virulence and/or pathogenicity within fungal pathogens. We also describe the different complexes or mechanisms targeted by fungicides, thus addressing a relevant issue regarding diseases management. In spite of the controversial origin and evolution of fungal mt-genomes, the intrinsic mechanisms and molecular biology involved in their evolution will help to understand at the molecular level the strategies for fungal disease management